STRENGTHENING PAKISTAN’S COUNTER VIOLENT EXTREMISM (CVE) STRATEGIES: TOWARD EFFECTIVE DERADICALIZATION AND SOCIAL REINTEGRATION (Contemporary Journal of Social Science Review, 2025)
This study critically examines Pakistan’s ongoing Countering Violent Extremism (CVE) measures to propose actionable strategies for effectively deradicalizing and reintegrating terrorists into mainstream society. It provides a comprehensive analysis of the roots of radicalization within Pakistan, tracing the socio-political, religious, and historical factors that have fostered extremism over time. The research evaluates existing counterterrorism (CT) strategies and deradicalization programs, identifying their limitations, particularly the overreliance on coercive, military-based approaches that have yielded short-term gains but failed to produce sustainable societal transformation.Drawing upon the Saudi Arabian PRAC (Prevention, Rehabilitation, and Aftercare) model as a comparative case study, this paper highlights critical gaps in Pakistan’s current framework and demonstrates how soft-power mechanisms, such as religious re-education, psychological counseling, community engagement, and socio-economic reintegration can enhance the effectiveness of its CVE initiatives. Through a qualitative comparative analysis, the study underscores the pivotal role of religious scholars, families, civil society, and educational institutions in preventing radicalization and supporting post-rehabilitation reintegration.The findings reveal that a multidimensional, community-driven approach is essential to achieving lasting peace and ideological transformation. Consequently the research recommends a strategic policy shift from reactive military responses to proactive, human-centric CVE interventions that promote tolerance, coexistence, and resilience against extremist ideologies. These insights aim to inform policymakers, practitioners, and scholars seeking to strengthen Pakistan’s national security and social harmony through sustainable deradicalization and reintegration efforts.